Furin-responsive triterpenine-based liposomal complex enhances anticervical cancer therapy through size modulation. (1st January 2020) - Chen, Yunyan; Guo, Mengfei; Qu, Ding; Liu, Yuping; Guo, Jian; Chen, Yan
Abstract: The accumulation and penetration of antitumor drugs in tumor tissues are directly related to their antitumor effects. The particle size of the nanodrug delivery system is one of the most important factors for the accumulation and penetration of antitumor drugs within tumor tissues. Generally, nanodelivery systems of intermediate size (100–120 nm) are capable of efficient accumulation owing to prolonged circulation and enhanced permeability and retention (EPR) effect; however, smaller ones (20–40 nm) are effective for deep penetration within tumor tissue. Currently a conventional drug delivery system cannot possess two types of optimal sizes, simultaneously. To solve this and to enhance cervical cancer treatment, a furin-responsive triterpenine-based liposomal complex (PEGcleavable Tf-CTM/L), with Tf-CTM (transferrin-modified tripterine-loaded coix seed oil microemulsion) in core, coated with a thermo-sensitive lipid and a kind of PEG shell modified with a furin-cleavable peptide was developed to improve tumor-specific accumulation and penetration. Herein, PEGcleavable Tf-CTM/L was capable of efficient accumulation because of EPR effect. The PEG shells could timely detach under stimulation of overexpressed furin protein to solve the problem of the steric hindrance dilemma. The small-sized Tf-CTM released under stimulation of tumor microthermal environment in cervical cancer, which was efficient with regards to deep penetration at tumor sites. Notably, compared to the use of triterpenine alone, PEGcleavable Tf-CTM/L promoted anticervical efficacy and displayed diminished systemic toxicity by efficient accumulation and deep penetration of antitumor drugs within tumor tissues. Our study provides a new strategy, and holds promising potential for anticervical cancer treatment.